Formal techniques for effective co-verification of hardware/software co-designs - Mukherjee, R; Purandare, M; Polig, R; Kroening, D (Association for Computing Machinery, 2017)
Verification is indispensable for building reliable of hardware/software co-designs. However, the scope of formal methods in this domain is limited. This is attributed to the lack of unified property specification languages, the semantic gap between hardware and software components, and the lack of verifiers that support both C and Verilog/VHDL. To address these limitations, we present an approach that uses a bounded co-verification tool, HW-CBMC, for formally validating hardware/software co-designs written in Verilog and C. Properties are expressed in C enriched with special-purpose primitives that capture temporal correlation between hardware and software events. We present an industrial case-study, proving bounded safety properties as well as discovering critical co-design bugs on a large and complex text analytics FPGA accelerator from IBM.